Foetal Wastage and the Future of Cattle Production in Nigeria: A Review - Ahmad, Mustapha Yusif (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Livestock remains an essential and integral component of Nigeria's agriculture and vital to the socio-economic and food security of the country. Bovine, the most prominent ruminant animal, serves as a source of household income, food security, draft power, transportation, revenue generation, employment opportunities and a well-balanced agricultural system through manure production and utilization of forages, which are of no value to man but converted to useful products. These resources were mismanaged through indiscriminate slaughter of breeding stock and subsequent foetal wastages across abattoirs, which serves as a center of the practice. This unhealthy and unethical practice results to the depletion of national herd size with poor replacement capacity. The review report focuses on the reported cases of gravid bovine slaughter and foetal damages in the registered abattoirs across the country. Lack of post-mortem examinations, crude facilities/equipment, farmer’s ignorance of pregnancy and developmental stages of the animal, poor management practices, poor or lack of implementations of international meat act, lack of law at state or national level that offer protection of pregnant animals were among the factors that accelerate the practice in the country. This practice is a threat to the livestock industry, which must be addressed through proper conservation programmes for substantial benefits of the livestock sector. Laws must be enacted with strict penalties to the principal actors to safe guard the livestock and meat industry in general.